Total Factor Productivity and the Role of Entrepreneurship - Hugo Erken; Piet Donselaar; Roy Thurik (Tinbergen Institute, 2009)
Total factor productivity of twenty OECD countries for a recent period (1971-2002) is explained using six different models based on the established literature. Traditionally, entrepreneurship is not dealt with in these models. In the present paper it is shown that – when this variable is added - in all models there is a significant influence of entrepreneurship while the remaining effects mainly stay the same. Entrepreneurship is measured as the business ownership rate (number of business owners per workforce) corrected for the level of economic development (GDP per capita).
Keywords: E20; L26; M13; O10; O30; O40; O50; 330; Total factor productivity; research and development; entrepreneurship; OECD; Produktivität; Entrepreneurship-Ansatz; Selbstständige; Forschung; OECD-Staaten